MiR-669a-5p promotes adipogenic differentiation and induces browning in preadipocytes. (31st December 2022) - Tan, Xiaoqiong; Zhu, Tingting; Zhang, Linqiang; Fu, Lin; Hu, Ying; Li, Huiqin; Li, Chengbin; Zhang, Jingjing; Liang, Bin; Liu, Jing
ABSTRACT: Obesity is a major global health issue that contributes to the occurrence of metabolic disorders. Based on this fact, understanding the underlying mechanisms and to uncover promising therapeutic approaches for obesity have attracted intense investigation. Brown adipose tissue (BAT) can help burns excess calories. Therefore, promoting White adipose tissue (WAT) browning and BAT activation is an attractive strategy for obesity treatment. MicroRNAs (miRNAs) are small, non-coding RNAs, which are involved in regulation of adipogenic processes and metabolic functions. Evidence is accumulating that miRNAs are important regulators for both brown adipocyte differentiation and white adipocyte browning. Here we report that the expression of miR-669a-5p increases during the adipogenic differentiation of 3T3-L1 and C3H10T1/2 adipocytes. miR-669a-5p supplementation promotes adipogenic differentiation and causes browning of 3T3-L1 and C3H10T1/2 cells. Moreover, the expression of miR-669a-5p is upregulated in iWAT of mice exposed to cold. These data demonstrate that miR-669a-5p plays a role in regulating adipocyte differentiation and fat browning. Abbreviations : Acadl : long-chain acyl-Coenzyme A dehydrogenase; Acadm : medium-chain acyl-Coenzyme A dehydrogenase; Acadvl : very long-chain acyl-Coenzyme A dehydrogenase, very long chain; Aco2 : mitochondrial  aconitase 2; BAT: brown adipose tissue; Bmper : BMP-binding endothelial regulator; Cpt1-b :carnitine palmitoyltransferase 1b; Cpt2 : carnitine palmitoyltransferase 2; Crat : carnitine acetyltransferase; Cs : citrate synthase; C2MC: Chromosome 2 miRNA cluster; DMEM: Dulbecco's modified Eagle medium; eWAT: epididymal white adipose tissue; ETC: electron transport chain; FAO: fatty acid oxidation; Fabp4 :fatty acid binding protein 4; FBS: fetal bovine serum; Hadha : hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex subunit alpha; Hadhb : hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex subunit beta; HFD: high fat diet; Idh3a : isocitrate dehydrogenase 3 alpha; iWAT: inguinal subcutaneous white adipose tissue; Lpl : lipoprotein lipase; Mdh2 : malate dehydrogenase 2; NBCS: NewBorn Calf Serum; mt-Nd1 : mitochondrial NADH dehydrogenase 1; Ndufb8 :ubiquinone oxidoreductase subunit B8; Nrf1 : nuclear respiratory factor 1; Pgc1α : peroxisome proliferative activated receptor gamma coactivator 1 alpha; Pgc1b : peroxisome proliferative activated receptor, gamma, coactivator 1 beta; Pparγ : peroxisome proliferator activated receptor gamma; Prdm16 : PR domain containing 16; Rgs4 : regulator of G-protein signaling 4; Sdhb : succinate dehydrogenase complex, subunit B; Sdhc : succinate dehydrogenase complex, subunit C; Sdhd : succinate dehydrogenase complex, subunit D; Sh3d21 : SH3 domain containing 21; Sfmbt2 : Scm-like with four mbt domains 2; TG: triglyceride; TCA: tricarboxylic acid cycle; Tfam : transcription factor A, mitochondrial; TMRE: tetramethylrhodamine, methyl ester; Ucp1 : uncoupling protein 1; Uqcrc2 : ubiquinol cytochrome c reductase core protein 2; WAT: White adipose tissue